Persepsi Masyarakat Tentang Kemacetan Lalu Lintas di Jakarta - Haryono, Haryono; Darunanto, Danang; Wahyuni, Rr. Endang (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2018)
The aim of this research is to identify public opinion about the suitable modern public transportation modes in Jakarta. Transportation is inseparable from traffic jam which also affects the residential areas. Traffic jam is a stagnant situation caused by the number of vehicles exceeding the road’s capacity. Traffic congestion becomes daily problem in Jakarta and other cities in Indonesia. This research used qualitative method. The result of this research shows that traffic congestion in Jakarta was caused by large number of private vehicles. Due to that condition, the suitable public transportation modes are, Monorail, TransJakarta bus, Tram, MRT, and LRT. 48% of Jakarta citizens chose monorail as the most suitable transportation while 38% of them preferred Transjakarta bus, and 14% of people asked for tram. The expectation of the realization of modern transportation mode, in this case monorail, is to decrease the number of private vehicles. Therefore, the traffic congestion in Jakarta are able to be reduced.